SISTEM PAKAR BERBASIS WEB UNTUK DIAGNOSIS JENIS PENYAKIT DIABETES MENGGUNAKAN METODE CERTAINTY FACTOR STUDI KASUS RSAB HARAPAN KITA - Rudi Hartono; Susanna Dwi Yulianti Kusuma (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
The development of Information and Communication Technology has brought significant transformations to the medical field, one of which is through the utilization of expert systems. The primary problem addressed in this research is the high prevalence of diabetes mellitus, which is often diagnosed too late due to a lack of public knowledge regarding early symptoms and the limited number of medical specialists. This condition increases the risk of serious complications and mortality. The objective of this study is to design and develop a web-based expert system capable of   performing early diagnosis of potential diabetes and providing educational information about its symptoms to the public and non-specialist medical personnel. The method used in the development of this system is the Certainty Factor (CF). This method was selected for its ability to accommodate data uncertainty by assigning confidence values to each symptom based on expert knowledge. The system processes the symptoms entered by the user and displays the diagnosis results sorted by the highest certainty value (descending). The result of this research is a web-based expert system application that serves as an early screening tool at RSAB Harapan Kita. This system is expected to facilitate easier access to information, accelerate the initial diagnosis process, and assist the community in the accurate prevention and early management of diabetes mellitus